On Quantum Efficiency Measurements and Plasmonic Antennas - Matsuzaki, Korenobu; Liu, Hsuan Wei; Götzinger, Stephan; Sandoghdar, Vahid (ACS Photonics, 2021)
Quantum efficiency is a key quantity that describes the performance of light-emitting materials and is, thus, an important metric for assessing novel nanophotonic systems. This Perspective provides a concise discussion of the difficulties encountered in the characterization of quantum efficiencies, especially for studies that involve single emitters. In particular, we review various approaches that have been recently used for determining quantum efficiencies of emitters coupled to plasmonic antennas and highlight the subtleties and challenges that hinder precise measurements.
CRIS-Team Scopus Importer:2021-06-25
Keywords: antenna; plasmonic; Purcell enhancement; quantum efficiency; quenching; spontaneous emission